The Effect of Family Ownership On Accrual-Based and Real Activities Based Earnings Management: Evidence from The French Context - Zeineb Feki Cherif; Salma Damak Ayadi; Saoussen Boujelben Ben Hamad (Journal of Accounting and Management Information Systems (JAMIS), 2020)
Research Question: What is the effect of family ownership on accrual-based earnings management (ABEM) and on real earnings management (REM)? Motivation: Despite the importance and the predominance of family companies among the worldwide listed firms, there is a few study having examined earnings management in family businesses when compared to non-families ones. Their particular characteristics distinguishing them from typical public companies, family firms could provide an interesting setting for the purpose of investigating their earnings quality. Idea: Using agency theory and socio-emotional wealth (SEW) theory, we suggested and explained the impact of family ownership on earnings management. Data: We analyze a sample of French firms listed in CAC All-Tradable index in the period ranging from 2014 to 2016. Tools: We adopts the Generalized Least Squared (GLS) technique correcting heteroskedasticity and serial correlation problems related to panel data. Findings: We document that family ownership has no significant effects on ABEM, but it has a positive and significant influence on REM. In fact, this study conducted on French family firms shows that they are more involved in upward earnings management than non-family firms. Our results supports the hypothesis that family firms suffer from type II agency problems, and it can be explained by the desire to ensure the control and influence among the firm. Contributions: This study is expected to increase the understanding of the family firms' behavior in terms of their earnings management practices building on the both agency and SEW theory.
Keywords: M41; 650; family ownership; accrual-earnings management; real earnings management; agency problem; socio-emotional wealth